Culture and tourism-led peri-urban transformation in China – The case of Shanghai - Li, Jie (Cities, 2020)
Culture and tourism occupy an important position in urban development strategy in both Global North and South. While most studies on culture-led development in China focus on inner city regeneration, little research has been conducted on peri-urban transformations under culture- and tourism-led approach. With two case studies in peri-urban Shanghai, this research critically examines in detail why and how culture-led development planned and implemented under the specific local context and critically reflects the implications on peri-urban transformation. Engaged with the literature on cultural instrumentisation and urban thematisation in an entrepreneurial city, this paper argues that culture-led peri-urban development in Shanghai were initiated by the local state, to serve multiple purposes of boosting land price, building a prestigious image attracting investors and tourists, and fostering cultural and creative industries. However, more often than not, culture was only harnessed as a ‘buzz word’ that provides a justification for large-scale land development, and planned cultural creative industries zones were often reduced to places for leisure and tourism based consumption. •Examining culture- and tourism led peri-urban transformation in Shanghai new towns•Cultural projects are expected to act as flagships to facilitate land selling.•Plans to foster new cultural creative industries are hardly successful.•Interventions aimed at cultural production are always reduced to consumption based on leisure and tourism.